The effects of thyme (Thymus vulgaris L.) oil concentration on liquid-smoked vacuum-packed rainbow trout (Oncorhynchus mykiss Walbaum, 1792) fillets during chilled storage - Alcicek, Zayde (Elsevier Sci Ltd, 2011)
This study examined the effects of thyme oil on chemical properties, microbiological changes, and sensory quality in vacuum-packed liquid-smoked rainbow trout fillets under chilled storage. After 150 days of storage, the total volatile basic nitrogen (TVB-N) values were 30.52, 27.5 and 39.43 mg/100 g, and total viable counts (TVC) were 5.34, 4.96 and 5.53, for thyme oil additions of 10 (T10), 50 (T50) and 0 (control; TO) mL/L brine, respectively. The highest acceptable TVB-N value was adopted as 30 mg /100g. corresponding to shelf lives of 135, 150, and 105 days for T10, 150, and TO, respectively. T50 addition of thyme oil to liquid-smoked rainbow fillets extended shelf life 110 and T50, gave acceptable sensory quality and limited microbiological growth during chilled storage. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Thyme oil; Liquid smoke; Polycyclic aromatic hydrocarbons; Rainbow trout; Sensory quality; Spices